Locally ϕ-Symmetric Generalized Sasakian-Space Forms - Sarkar, A.; Sen, M. (Український математичний журнал, 2013)
The aim of the present paper is to find necessary and sufficient conditions for locally ϕ-symmetric generalized Sasakian-space forms to have constant scalar curvature, η -parallel Ricci tensor, and cyclic parallel Ricci tensor. Illustrative examples are given. Встановлено необхідні та достатні умови, при яких локально ϕ-симетричні узагальнені форми простору Сасакяна мають сталу скалярну кривизну, η-паралельний тензор Річчі та циклічний паралельний тензор Річчі. Наведено приклади.